What determines whether preferential liberalization of barriers against foreign investors in services are beneficial or immizerising: Application to the case of Kenya - Edward J. Balistreri; Jesper Jensen; David Tarr (Economics: The Open-Access, Open-Assessment E-Journal, 2015)
Despite the fact that many modern preferential trade agreements include commitments to foreign investors in imperfectly competitive services sectors, the literature has not established conditions under which these agreements are beneficial or harmful. The authors fill that void by developing a model with monopolistic competition and foreign direct investment in services with Dixit-Stiglitz endogenous productivity effects from additional varieties. They specify a numerical model, with probability distributions of all parameters. The model is executed 30,000 times, and results are reported as probability of an outcome, based on the sample distribution. In order to ground the results in reality, the authors apply the model to Kenya. They show that preferential commitments in services could be immizerising. Losses are more likely the greater the share of initial rent capture on the services barriers in the home country and the more technologically advanced are the excluded regions relative to the partner region.
Keywords: F12; F13; F14; F15; F23; F47; C68; L16; 330; immizerising services liberalization; preferential liberalization; multinationals; monopolistic competition; foreign direct investment; endogenous productivity effects